Collaborative elearning: an academic experience between the University of Costa Rica and the University of Kansas / Colaboración en línea: una experiencia académica entre la Universidad de Costa Rica y la Universidad de Kansas - Allen Quesada Pacheco (Actualidades Investigativas en Educación)
The continuing improvements in the worldwide access to the Internet are rapidly improving the ability forinternational collaborative eLearning. The University of Kansas (KU) and University of Costa Rica (UCR) aredeveloping eLearning strategies designed to establish meaningful and sustained relationships. We are investigating:1) how to use technology and pedagogy to enrich social interaction and learning, 2) strategies and technologies forengaging students in collaborating on issues of mutual interest, 3) understanding how the quality of relationships canimprove learning, 4) institutional issues and barriers related to implementing coursework, certifications and academicprograms across international institutions. Our analysis indicates that student collaborate more when they can meetin live teleconferencing as opposed to relying solely of asynchronous email or threaded discussions for collaborativeproject. Participantsreported that strategies that scaffold activities by beginning with clearly stated problems andachievable common goals, such as locating and ranking relevant web resources, contribute to richer collaborations.